Co‐morbidities and bleeding in elderly patients with haemophilia—A survey of the German, Austrian and Swiss Society of Thrombosis and Haemostasis Research (GTH). Issue 5 (21st June 2017) - Miesbach, W.; Reitter‐Pfoertner, S.‐E.; Klamroth, R.; Langer, F.; Wolf, H.‐H.; Tiede, A.; Siegmund, B.; Scholz, U.; Müller, P. R.; Eichler, H.; Pabinger, I.
Abstract : Background: Nowadays patients with haemophilia survive longer due to improvements in haemophilia care. It has been hypothesized that the bleeding type and frequency may vary with age and are influenced by co‐morbidities and co‐medication in elderly patients. Objectives: To investigate a large group of patients older than 60 years of age with haemophilia concerning haemophilia treatment, bleeding pattern changes, co‐morbidities, co‐medication, bleeding sites and patient mortality. Methods: A retrospective multi‐centre data collection study was initiated on behalf of the German, Austrian and Swiss Society of Thrombosis and Haemostasis Research (GTH). Parameters of interest were investigated over the 5 years prior to study entry. Results: A total of 185 haemophilia patients (mean age, 69.0±7.0 years, 29% with severe haemophilia) were included in the study. Regular prophylaxis was performed in 30% of the patients with severe haemophilia. In total, the annual bleeding rate was 2.49 and in patients with severe haemophilia 5.61, mostly caused by joint bleeds. Hypertension was the most common co‐morbidity, but it occurred significantly less frequently than in an age‐matched general population older than 70 years; 12% of the patients suffered from ischaemic heart disease, and 13% of the patients received anticoagulant or antiplatelet therapy. Within the observation period, 17% of the patients with severe haemophilia developed a higher frequency of bleeding symptoms, which was significantly associated with the use of antiplatelet or anticoagulant drugs. Conclusions: The most common co‐morbidity of the patient population was hypertension, a considerable part had ischemic heart disease and antiplatelet or anticoagulant drugs.